Baseline risk factors of in-hospital mortality after surgery for acute type A aortic dissection: an ERTAAD study - Biancari, Fausto; Demal, Till; Nappi, Francesco; Onorati, Francesco; Francica, Alessandra; Peterss, Sven; Buech, Joscha; Fiore, Antonio; Folliguet, Thierry; Perrotti, Andrea; Hervé, Amélie; Conradi, Lenard; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Surgery for type A aortic dissection (TAAD) is associated with high risk of mortality. Current risk scoring methods have a limited predictive accuracy. Methods: The subjects of the present analysis were patients who underwent surgery for acute TAAD at 18 European centers of cardiac surgery from the European Registry of Type A Aortic Dissection (ERTAAD). Results: Out of 3902 patients included in the ERTAAD, 2477 patients fulfilled the inclusion criteria of the present analysis. In the validation dataset (2229 patients) the rate of in-hospital mortality was 18.4%. The rate of composite outcome (in-hospital death, stroke/global ischemia, dialysis and/or acute heart failure) was 41.2% and 10-year mortality was 47.0%. Logistic regression identified the following patient-related variables associated with an increased risk of in-hospital mortality (AUC 0.755, 95%CI 0.729-0.780; Brier score 0.128): age, estimated glomerular filtration rate (eGFR), arterial lactate, iatrogenic dissection, left ventricular ejection fraction≤50%, invasive mechanical ventilation, cardiopulmonary resuscitation immediately before surgery and cerebral, mesenteric and peripheral malperfusion. The estimated risk score was associated with an increased risk of composite outcome (AUC 0.689, 95%CI 0.667-0.711) and of late mortality (HR 1.035, 95%CI 1.031-1.038; Harrell’s C 0.702; Somer’s D 0.403). In the validation dataset (248 patients), the in-hospital mortality rate was 16.1%, that of composite outcome was 41.5% and 10-year mortality rate was 49.1%. The estimated risk score was predictive of in-hospital mortality (AUC 0.703, 95%CI 0.613-0.793; Brier score 0.121; slope 0.905) and of composite outcome (AUC 0.682, 95%CI 0.614-0.749). The estimated risk score was predictive of late mortality (HR 1.035, 95%CI 1.031-1.038; Harrell’s C 0.702; Somer’s D 0.403), also when hospital deaths were excluded from the analysis (HR 1.024, 95%CI 1.018-1.031; Harrell’s C 0.630; Somer’s D 0.261). Conclusions: The present analysis identified several baseline clinical risk factors, along with preoperative estimated glomerular filtration rate and arterial lactate, which are predictive of in-hospital mortality and major postoperative adverse events after surgical repair of acute TAAD. These risk factors may be valuable components for risk adjustment in the evaluation of surgical and anesthesiologic strategies aiming to improve the results of surgery for TAAD.